Assessing politeness of requestive speech acts produced by Japanese learners of English in a spoken corpus - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Aika Miura Tokyo University of Agriculture, Japan   ABSTRACT This study aims to investigate whether it is possible to assess learners' sociopragmatic competence in learner spoken data by examining requests produced by Japanese learners of English. Various pragmalinguistic features of requests in shopping role plays in the National Institute of Information and Communications Technology Japanese Learner English (NICT JLE) Corpus were extracted and the appropriateness of these linguistic features was rated by twenty English language instructors (10 native speakers and 10 Japanese) in terms of their politeness in different shopping situations. A significantly high rate of agreement was only obtained in judging the requests negotiating for a refund or exchange of the purchased item. The Japanese informants showed a relatively lower agreement than the natives especially on requests asking for permission to test an item. The highly rated linguistic features were not frequently used in the corpus. Therefore, annotating the sociopragmatic information in the target corpus seems unrealistic.